The Smart Home Control System based on Raspberry Pi - Jiang, Ronghua (Journal of Research in Science and Engineering, 2025)
With the development of Internet of Things and sensor network technology, the implementations of smart home control system have become more various than before. In this paper, a new smart home control system based on Raspberry Pi is proposed, with the features of human movement alert, temperature and humidity monitor as well as outlet control. The system is available for both desktop and mobile platforms, enhancing the security of the house and providing more convenience to the user.